Preparation method and application of PET (Polyethylene Terephthalate) enhanced bi-crosslinking polyion liquid composite solid electrolyte
By modifying nano zinc oxide particles on PET non-woven fabrics and step-by-step crosslinking of functionalized alkenyl ionic liquids, PET enhanced double crosslinked polyion liquid composite solid electrolyte was prepared, which solved the shortcomings in performance and preparation methods of PET non-woven fabric-based electrolytes, and achieved solid electrolytes with high mechanical strength, excellent electrochemical properties and good thermal stability.
Patent Information
- Application Number
- CN202411831326.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing PET nonwoven fabric-based solid polymer electrolytes are difficult to balance in terms of mechanical strength, porosity, film thickness and electrochemical properties, and the preparation method is complex and uses more components.
The preparation method of PET enhanced dual crosslinked polyion liquid composite solid electrolyte is adopted to make functional PET non-woven fabrics by selecting PET fibers of suitable fiber diameters, and the step-by-step crosslinking of functionalized alkenyl ionic liquids is formed by modifying nano zinc oxide particles and forming a high-performance solid electrolyte.
It significantly improves the mechanical properties, ionic conductivity, electrochemical windows and thermal stability of solid electrolytes, ensuring the safety and cycling stability of the battery.
Smart Images

Figure CN119640587A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer solid electrolyte preparation, and in particular to a preparation method and application of a PET reinforced double-crosslinked polyionic liquid composite solid electrolyte. Background Art
[0002] Currently, lithium-ion batteries contain low-flash point solvents. If leaked, they may cause problems such as battery combustion. In addition, lithium dendrites produced by lithium deposition at the negative electrode may puncture the lithium-ion battery separator, causing a short circuit between the positive and negative electrodes and resulting in circuit board combustion.
[0003] In view of the safety issues of liquid lithium-ion batteries, gel polymer lithium-ion battery technology and solid polymer lithium-ion battery technology have gradually emerged, which mainly rely on gel or solid electrolytes for lithium ion conduction. This type of lithium-ion battery has a good solid-solid interface, which can effectively prevent the safety problems caused by liquid batteries. It also has the advantages of being lighter, thinner, and having a higher energy density, becoming an important research direction to replace liquid lithium-ion batteries.
[0004] Polymer solid electrolytes have the advantages of high flexibility, low interfacial impedance and low production cost, but they need to solve the problems of low mechanical strength, low electrical conductivity and poor thermal stability.
[0005] Non-woven fabrics have excellent thermal stability and unique three-dimensional pore structure, which can provide protection for battery safety. At the same time, they are conducive to the full filling of solid electrolyte materials and reduce interfacial resistance, making non-woven fabrics a good film for solid polymer lithium-ion batteries, especially a good carrier for energy storage and power batteries with long cycle life requirements.
[0006] At present, some studies have disclosed the components and preparation methods of PET non-woven fabric-based solid polymer electrolytes. Since the presence of PET non-woven fabrics can improve the mechanical strength and thermal stability of solid polymer electrolytes, PET non-woven fabrics have naturally large pore sizes and high porosity. In order to prevent lithium dendrites from piercing the membrane, its thickness must be increased, which makes it impossible to simultaneously meet the requirements of lithium-ion batteries for thinner thickness and greater strength.
[0007] At present, PET non-woven fabric-based solid polymer electrolytes mainly improve ionic conductivity by optimizing the composition of polymer electrolytes, improve interfacial contact by optimizing the composite method of polymer electrolytes and non-woven fabrics, and further improve thermal stability, mechanical strength, ionic conductivity and other properties; but few have started from both the composition of PET non-woven fabrics and polymer electrolytes at the same time to prepare PET non-woven fabric-based solid polymer electrolyte films that are thinner, have higher mechanical strength, higher porosity, better ionic conductivity, and higher electrochemical stability window.
[0008] In the published patent CN105811005A, the non-woven fabric substrate is immersed in a polymer emulsion, so that the effective ingredients in the polymer emulsion enter the pores in the non-woven fabric substrate, and then dried to obtain a polymer electrolyte. The results show that the polymer electrolyte has a high ionic conductivity and lithium ion migration number, and has excellent heat resistance and mechanical strength.
[0009] However, this patent mainly discloses the preparation method of polymer emulsion, and the non-woven fabric is only used as a matrix, and the role of the non-woven fabric in the strength and ionic conductivity of the polymer electrolyte is not highlighted.
[0010] In the published patent CN110120548A, an electrolyte slurry containing a cross-linkable copolymer, a lithium salt, a cross-linking agent, inorganic nanoparticles and a photoinitiator is coated on a non-woven fabric and dried to form a film, and then cured and cross-linked under ultraviolet light to form a polymer electrolyte layer on the non-woven fabric; wherein the non-woven fabric is modified with a silane coupling agent containing carbon-carbon unsaturated double bonds.
[0011] Although compared with conventional non-woven fabrics, non-woven fabrics modified with silane coupling agents having carbon-carbon unsaturated double bonds can enable the polymer electrolyte layer and the non-woven fabric layer to be bonded to each other through chemical bonding, which helps to improve ion transmission, the method of directly preparing non-woven fabrics modified with silane coupling agents is time-consuming, complicated to operate, and involves processes such as solvent recovery, which is not conducive to promoting its industrialization.
[0012] In the published patent CN113363573A, the first electrolyte slurry and the second electrolyte slurry of the non-woven fabric are separated, and the second electrolyte slurry is in-situ polymerized into a membrane in the pores of the non-woven fabric, so that the first electrolyte membrane and the second electrolyte membrane are in close contact with each other, without obvious stratification, with good integrity and the advantage of high ionic conductivity.
[0013] This patent only uses the method of preparing electrolyte slurry in batches, and then casting the slurry onto the surface of non-woven fabric to form a solid electrolyte. The non-woven fabric used has the disadvantage of low strength of conventional non-woven fabrics of this characteristic, and the solid electrolyte formed is mainly the physical combination of the non-woven fabric and the electrolyte slurry, and a small amount of polymerization reaction, so the performance of the solid electrolyte is poor.
[0014] In the published patent CN117638214A, a PET non-woven fabric is immersed in a polymer electrolyte precursor solution containing a polymer matrix, a plasticizer, and a lithium salt, left to stand under vacuum, taken out and placed between two substrates, and cured with ultraviolet light to obtain a PET non-woven fabric-based polymer electrolyte; the results show that the composite PET non-woven fabric has excellent thermal stability and greatly improves the tensile strength and puncture strength of the polymer electrolyte.
[0015] This patent mainly improves the composition and preparation process of the electrolyte precursor solution, but does not make major improvements to the PET non-woven fabric. The process of forming a solid electrolyte is relatively conventional and does not increase the degree of cross-linking between the electrolyte precursor solution and the PET non-woven fabric.
[0016] In the published patent CN117175140A, in order to solve the problem that non-woven fabrics have naturally large pores and high porosity and cannot be directly used as battery separators, a layer of polymer pore layer with smaller pores is loaded on the non-woven fabric to improve the pore size and porosity of the non-woven fabric while maintaining its heat resistance, thereby preparing a battery separator with better performance.
[0017] Although the patent discloses that PET non-woven fabrics may contain inorganic fillers, the modification process of the PET non-woven fabrics is not described in detail, and the process of preparing the battery separator mainly involves improving the casting liquid, which is then coated on the surface of the non-woven fabric. However, the preparation method is complicated and involves a large amount of solvents, and no highly cross-linked structure is formed between the casting liquid and the PET non-woven fabric.
[0018] In the published patent CN118146600A, in order to solve the problem of poor thermal stability and flame retardancy of battery diaphragm materials, a fluorine-containing polymer is provided as a diaphragm matrix (equivalent to non-woven fabric), and a battery diaphragm material is prepared using nanomaterials such as zinc oxide and carbon nanotubes, functional polymers, and polytetrafluoroethylene binders.
[0019] Although the patent discloses the use of zinc oxide nanomaterials and a diaphragm matrix composite, its implementation process uses a large number of auxiliary components and a relatively complex composite process, and the diaphragm matrix does not use PET non-woven fabrics or other non-woven fabrics. Therefore, it has high process requirements and puts great pressure on environmental protection, and the formed diaphragm is an atypical battery diaphragm material.
[0020] Therefore, based on the above background and problems, it is necessary to form a preparation method for PET non-woven fabric with thin film thickness and good comprehensive performance under the condition of ensuring good mechanical strength and porosity of the PET non-woven fabric, and to form a preparation method for solid polymer electrolyte in which the electrolyte precursor solution is not only combined with the PET non-woven fabric in physical form, but also can be highly polymerized in the chemical form of cross-linking and polymerization, thereby improving the comprehensive performance of the solid polymer electrolyte such as ionic conductivity, electrochemical window, thermal stability, etc. Summary of the invention
[0021] The present invention aims to solve the problems that the mechanical strength, porosity, film thickness and electrochemical performance of PET non-woven fabric-based solid polymer electrolytes prepared in the prior art are difficult to balance, the preparation method is relatively complex and relatively more components are used. A preparation method of PET reinforced double cross-linked polyionic liquid composite solid electrolyte is provided. The preparation method comprises the following steps:
[0022] S10: taking PET fibers, including first PET fibers and second PET fibers, wherein the first PET fibers have a greater aspect ratio than the second PET fibers, mixing the first PET fibers with the second PET fibers, and adding a dispersant, a defoaming agent, and water to dissolve the fibers to form a functional fiber slurry;
[0023] S20: preparing the functional fiber slurry into PET base paper, and drying and hot pressing in sequence to form PET non-woven base paper;
[0024] S30: configuring and forming a nano zinc oxide particle dispersion, and performing a dispersion treatment, and then immersing the PET non-woven fabric base paper in the nano zinc oxide particle dispersion, and performing a heat treatment to form a functional PET non-woven fabric;
[0025] S40: configuring a functionalized olefinic ionic liquid, adding a crosslinking agent, a lithium salt, a plasticizer and a photoinitiator thereto, mixing and dispersing them uniformly, and obtaining an electrolyte precursor solution; placing the functional PET nonwoven in the electrolyte precursor solution, and allowing it to stand and immerse under vacuum conditions to obtain an initial solid electrolyte;
[0026] S50: thermally polymerizing the initial solid electrolyte to obtain a thermally polymerized solid electrolyte, and then photopolymerizing the initial solid electrolyte to obtain the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte.
[0027] Optionally, the diameter of the first PET fiber is 2 μm to 5 μm, and the diameter of the second PET fiber is 3 μm to 10 μm.
[0028] Optionally, the mass ratio of the first PET fiber to the second PET fiber is 3:7 to 7:3.
[0029] Optionally, the mass ratio of the PET fiber in the functional fiber slurry is 1% to 3%; the mass ratio of the dispersant relative to the PET fiber is 0.1% to 1%; and the mass ratio of the defoaming agent relative to the dispersant is 45% to 55%.
[0030] Optionally, the nano zinc oxide particles are zinc oxide particles modified by a silane coupling agent.
[0031] Optionally, the functionalized alkenyl ionic liquid contains cations, and the cations are a mixture of any one or more of imidazolium ions, pyridinium ions, quaternary ammonium ions, quaternary phosphonium ions, pyrrolidine ions, and piperidine ions.
[0032] Optionally, the cation comprises -NH 2 , -SH, -NCO, -OH, -C=C- or -CH(O)CH-.
[0033] Optionally, based on the total mass of the electrolyte precursor solution, the mass content of each component in the electrolyte precursor solution is: 40% to 60% of functionalized olefinic ionic liquid, 10% to 20% of cross-linking agent, 10% to 15% of lithium salt, 20% to 30% of plasticizer, and 0.5% to 2% of photoinitiator.
[0034] Optionally, the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte satisfies at least one of the following conditions:
[0035] (A) an ionic conductivity of 1.0 mS / cm to 1.5 mS / cm;
[0036] (B) The electrochemical window is 5V to 6V;
[0037] (C) a tensile strength of 15 MPa to 35 MPa;
[0038] (D) a specific capacity of 150 mAh / g to 170 mAh / g;
[0039] (E) Impedance is 3.5Ω to 4.6Ω.
[0040] On the other hand, the present invention also proposes an application of a PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte, which is the application of the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte prepared according to the above preparation method in a gel polymer lithium ion battery or a solid polymer lithium ion battery.
[0041] The present invention selects PET fibers with suitable fiber diameters as main fibers and bonding fibers respectively, processes them through a specific process, and prepares PET non-woven base paper, and impregnates them with a specific nano zinc oxide particle dispersion to form a functional PET non-woven fabric. Based on the non-woven fabric, the functional PET non-woven fabric is cross-linked with an electrolyte precursor liquid and a functionalized olefinic ionic liquid in steps to prepare a PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte. Compared with the prior art, the beneficial effects are as follows:
[0042] (1) Improvement of mechanical properties: The functional PET non-woven fabric has a tensile strength of up to 20MPa to 30MPa and excellent mechanical properties. Through the step-by-step cross-linking process, the tensile strength and puncture strength are further improved, ensuring that it can resist the growth of lithium dendrites during the battery cycle, reduce the risk of short circuits such as lithium dendrite puncture, and support the composite solid electrolyte with excellent mechanical properties and electrochemical cycle performance;
[0043] (2) Improvement of ionic conductivity: Functional PET non-woven fabric has high porosity and excellent wettability. When the functional PET non-woven fabric is immersed in the polymer electrolyte precursor solution under a certain vacuum environment, all the pores in the functional PET non-woven fabric can be filled with the precursor solution, so that the porosity of the solid electrolyte after curing is almost zero, and the internal ion transmission channel is complete, so that the electrolyte has excellent ionic conductivity; in addition, due to the modification of zinc oxide particles on the functional PET non-woven fabric, the zinc oxide particles form the role of inorganic plasticizer in the polymer electrolyte, effectively reducing the crystallinity of the polymer matrix, thereby enhancing the lithium ion migration within the polymer chain and improving the ionic conductivity of the electrolyte;
[0044] (3) Improvement of electrochemical window: Since there are inorganic zinc oxide particles on the functional PET non-woven fabric, and zinc oxide particles have excellent chemical stability, they can effectively improve the oxidation stability of the composite solid electrolyte. High oxidation stability is a prerequisite for matching high-voltage positive electrodes. The improvement of the electrochemical window shows that solid electrolytes have the potential for practical application in high-voltage batteries.
[0045] (4) Improved thermal stability: Functional PET non-woven fabrics have excellent thermal stability. Compared with traditional PE and PP separators, they have a higher melting point and a lower shrinkage rate when kept warm for a period of time at high temperatures. They also have good flame retardant properties when compounded with polymer electrolytes, which significantly improves the safety performance of lithium-ion batteries. In addition, due to the stability of the imidazole ring of the functionalized olefinic ionic liquid and the strong double cross-linked network, the thermal stability of the composite solid electrolyte is further improved, which can effectively reduce the possibility of fire and explosion when the battery is under extreme conditions, thereby improving the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0047] Figure 1 is a process flow chart of a preparation method according to an embodiment of the present invention;
[0048] Figure 2 This is a physical picture of the functional PET nonwoven fabric prepared according to the embodiment of the present invention;
[0049] Figure 3 This is a (200×) SEM image of the functional PET nonwoven fabric prepared according to an embodiment of the present invention;
[0050] Figure 4 This is a (5000×) SEM image of the distribution state of nano zinc oxide particles of the functional PET non-woven fabric prepared according to the embodiment of the present invention;
[0051] Figure 5 is the structural formula of the functionalized olefinic ionic liquid of the imidazolyl cation-bis(trifluoromethanesulfonyl)imide system according to the embodiment of the present invention;
[0052] Figure 6 Schematic diagram of the synthesis process of forming VEIM-TFSI ionic liquid according to an embodiment of the present invention;
[0053] Figure 7 The electrochemical impedance spectra of Example ⑤ electrolyte and Example ⑥ electrolyte according to the implementation mode of the present invention;
[0054] Figure 8 Electrochemical window diagrams of Example ⑤ electrolyte and Example ⑥ electrolyte prepared according to the implementation mode of the present invention;
[0055] Fig. 9 Graphs showing stress-strain curves of Example ⑤ electrolyte and Example ⑥ electrolyte according to an embodiment of the present invention;
[0056] Fig.10 The symmetric Li||Li battery prepared by using the electrolyte of Example ⑤ and the electrolyte of Example ⑥ in the embodiment of the present invention is subjected to 0.5 mA -2 , 0.5mAhcm -2 The following cycle diagram;
[0057] Fig.11 Schematic diagram of the discharge curves and coulombic efficiency at 1C of the LFP full battery prepared with the electrolyte of Example ⑤ and the electrolyte of Example ⑥ according to the embodiments of the present invention.
[0058] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0059] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, inside, outside...) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0061] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0062] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0063] See also Figure 1 ; Figure 1 The present invention is a process flow chart of the preparation method according to the embodiment of the present invention.
[0064] The method for preparing a PET nonwoven fabric-based solid polymer electrolyte provided in an embodiment of the present invention comprises: Figure 1 The specific instructions are as follows.
[0065] Step S10:
[0066] Take PET fibers with a length of 5 mm to 10 mm, including first PET fibers with a diameter of 2 μm to 5 μm as trunk fibers, and second PET fibers with a diameter of 3 μm to 10 μm as bonding fibers. Add the first PET fibers and the second PET fibers into a deflaking barrel in a mass ratio of 3:7 to 7:3, and add dispersant, defoaming agent and water to form a mixture, and deflake at a rotation speed of 20,000 to 50,000 r to form a functional fiber slurry.
[0067] The two fibers were measured by differential scanning calorimetry (DSC) to obtain DSC curves, in which the trunk fiber had no obvious endothermic / exothermic peaks during the heating process, and only a sharp endothermic peak appeared at about 250°C to 260°C, indicating that the trunk fiber had a relatively high degree of crystallinity and good thermal stability; during the heating process of the bonding fiber, a glass transition first occurred at 70°C to 80°C, and then an exothermic peak appeared near 130°C with continued heating, and then an endothermic peak appeared at 250°C to 260°C with continued heating, indicating that the bonding fiber was a semi-crystalline polymer, which was easy to soften and deform after heating, and the characteristics of the bonding fiber determined that its crystallinity increased after heating. The characteristic of the bonding fiber to soften and deform after heating below the melting point was utilized to make the trunk fiber and the bonding fiber in the subsequently prepared PET non-woven fabric bonded to each other, thereby improving.
[0068] The mass ratio of the backbone fiber to the bonding fiber is 3:7 to 7:3, which is adjusted according to the balance between the tensile strength and the porosity of the subsequently made PET non-woven fabric; if there are too many backbone fibers, the bonding fiber will decrease, resulting in a decrease in the bonding effect, and the tensile strength of the PET non-woven fabric will decrease; if there are too few backbone fibers, the bonding fiber will increase, resulting in excessive bonding, and the porosity of the PET non-woven fabric will be too low; and the reason for the decrease in porosity is that the cylindrical bonding fibers become flat after being heated. Therefore, a suitable mass ratio of backbone fibers to bonding fibers can effectively improve the tensile strength of the PET non-woven fabric and adjust the appropriate porosity.
[0069] In this embodiment, the dispersant is one or more polyester dispersants or styrene maleic acid copolymers; the defoamer is one or more alcohol defoamers or polyether defoamers.
[0070] The mass ratio of the PET fiber in the mixture is 1% to 3%; the mass ratio of the dispersant to the PET fiber is 0.1% to 1%; and the mass ratio of the defoamer to the dispersant is 45% to 55%.
[0071] Step S20:
[0072] The functional fiber slurry is made into PET base paper using a paper sheet former, a press and a dryer. The tensile strength of the PET base paper is close to 0 MPa, the porosity is 75% to 85%, and the thickness is 45 μm to 55 μm. The drying temperature of the dryer is 130° C. to 150° C., preferably 140° C., and the drying time is 4 to 5 minutes.
[0073] Afterwards, a hot press is used to perform hot pressing at a temperature of 150°C to 180°C and a pressure of 0.2Mpa to 1Mpa to form a PET non-woven base paper. The PET non-woven base paper has a tensile strength of 10MPa to 16MPa, a porosity of 20% to 40%, and a thickness of 15μm to 20μm.
[0074] In this embodiment, the purpose of hot pressing is to increase the contact degree between PET fibers, increase the tensile strength of the PET non-woven base paper, and prevent it from spreading during subsequent impregnation.
[0075] Since the drying temperature of the dryer is 140°C, partial cold crystallization occurs inside the molecules of the bonding fiber, resulting in increased crystallinity and enhanced heat resistance of the bonding fiber. Therefore, in order to soften the PET fiber again, the temperature must be kept between 150°C and 250°C during hot pressing. Pressing PET fibers under softened conditions can increase the contact between fibers and increase tensile strength. In order to avoid excessive softening of PET fibers and too low porosity after pressing, it is not easy to use too high a temperature, so hot pressing uses a temperature of 150°C to 180°C.
[0076] Moreover, in the subsequent impregnation step, it is necessary to maintain an appropriate degree of contact of the PET nonwoven fabric, so the temperature setting of the hot pressing should not be too high. If the temperature is too high, the bonding fibers will be fully crystallized during the hot pressing stage and cannot provide favorable impregnation conditions. Similarly, too low a hot pressing pressure will result in a small degree of contact of the PET fibers, which may cause the impregnation to spread, while too high a pressure will result in an excessive degree of contact, making subsequent impregnation difficult to achieve. Therefore, the hot pressing pressure is selected to be 0.2Mpa to 1Mpa.
[0077] See also Figure 2 , Figure 3 and Figure 4 ; Figure 2 This is a physical picture of the functional PET nonwoven fabric prepared according to the embodiment of the present invention; Figure 3 This is a (200×) SEM image of the functional PET nonwoven fabric prepared according to an embodiment of the present invention; Figure 4 This is a (5000×) SEM image of the distribution state of nano zinc oxide particles of the functional PET non-woven fabric prepared according to an embodiment of the present invention.
[0078] Step S30:
[0079] A nano zinc oxide particle dispersion with a mass fraction of 1% to 5% is prepared, wherein the mass fraction of the solution depends on the impregnation amount of the PET non-woven base paper; and an ultrasonic cell disruptor is used to disperse the agglomerated nano zinc oxide particles.
[0080] Then, the PET nonwoven base paper is immersed in a nano zinc oxide dispersion having a solid content of 1.5% to 2.5% for 20s to 30s, and heat-treated at a temperature of 210° C. to 230° C. for 15min to 25min to form a functional PET nonwoven fabric (such as Figure 2After heat treatment, the weight of the nonwoven fabric increases by about 10%, the tensile strength of the functional PET nonwoven fabric is 20MPa to 30MPa, the porosity is 50% to 60%, and the thickness is 15μm to 20μm.
[0081] In this embodiment, the nano zinc oxide particles are zinc oxide particles or silane coupling agent modified zinc oxide particles with a particle size of 30 nm. The silane coupling agent modified zinc oxide particles contain active groups such as double bonds, epoxy, thiol and amino groups, and are more capable of forming a double cross-linking process with subsequent functionalized olefinic ionic liquids.
[0082] Impregnation with nano zinc oxide particle dispersion can improve tensile strength mainly because:
[0083] (1) The presence of nano-ZnO particles can play a role in heterogeneous nucleation, which is beneficial to improving the crystallinity of PET fibers while reducing the grain size, thereby increasing the tensile strength.
[0084] (2) Nano zinc oxide particles have a large specific surface area and are easily adsorbed between several molecular chains / fibers, thereby forming a cross-linked structure, which is conducive to dispersing stress and thus improving tensile strength.
[0085] Therefore, in this step, in order to make the nano zinc oxide particles fully combine with the PET fibers, it is necessary to enhance the effect of step S20 and increase the contact degree between the PET fibers. The appropriate contact degree can effectively improve the combination rate of the nano zinc oxide particles and the PET fibers.
[0086] If there is no enhancement effect of nano zinc oxide particles on the tensile strength of functional PET non-woven fabrics, all the tensile strength mechanical properties of functional PET non-woven fabrics come from the bonding effect of the bonding fibers, and it is necessary to increase the amount of bonding fibers or soften them fully, but both will bring negative effects:
[0087] (1) If the amount of bonding fiber is increased, the tensile strength may be improved and the porosity may be ensured by using mild hot pressing under lower temperature and pressure conditions, but this will not only increase the cost, but also increase the thickness of the PET nonwoven fabric because the diameter of the bonding fiber is greater than the diameter of the main fiber.
[0088] (2) If it is fully softened, medium to high heat pressing under higher temperature and pressure conditions may increase the tensile strength and reduce the thickness, but the cylindrical bonding fibers will become flat after heating, which will lead to a decrease in the porosity of the PET nonwoven fabric.
[0089] After adding nano zinc oxide particles, mild hot pressing can be performed under medium to low temperature and pressure conditions, giving priority to ensuring a thin thickness while improving tensile strength and porosity.
[0090] Step S40:
[0091] Functionalized olefinic ionic liquid, crosslinking agent, lithium salt, plasticizer and photoinitiator are configured and uniformly dispersed to obtain electrolyte precursor solution; functional PET nonwoven is arranged in the electrolyte precursor solution and vacuum is 1×10 4 Pa to 4×10 4 Pa and allowed to stand for 10 to 60 minutes to obtain an initial solid electrolyte.
[0092] In this embodiment, the cation in the functionalized alkenyl ionic liquid is a mixture of any one or more of imidazolium ions, pyridinium ions, quaternary ammonium ions, quaternary phosphonium ions, pyrrolidine ions, and piperidine ions, that is, the cation contains -C=C-, -NH 2 , -SH, -NCO, -OH or -CH(O)CH-, or more than one active group; in this embodiment, the compound that satisfies the above types of cation formation is a cationic compound.
[0093] See also Figure 5 ; Figure 5 The functionalized alkenyl ionic liquid structural formula of the imidazolyl cation-bis(trifluoromethanesulfonyl)imide system according to the embodiment of the present invention.
[0094] In this embodiment, the functionalized olefinic ionic liquid is an ionic liquid of an imidazolyl cation-bis(trifluoromethanesulfonyl)imide system, and the group of the nitrogen atom at position 1 in the imidazolyl cation ( Figure 8 The -X group in the ) is a carbene group containing -C=C- with 2 or more carbon atoms, and a group with a nitrogen atom at position 3 ( Figure 8 The -Y group in the formula (-Y) is a group that can react with double bonds, epoxy, thiol and amino active groups, i.e. -NH 2 , -SH, -NCO, -OH or -CH(O)CH- groups.
[0095] In this embodiment, the functionalized olefinic ionic liquid contains an anionic compound, which may be a mixture of any one or more of bis(trifluoromethanesulfonyl)imide, chlorine, bromine, iodine, tetrafluoroboric acid, hexafluorophosphoric acid, acetic acid, nitric acid, perchloric acid hydrogen sulfate, dihydrogen phosphate, trifluoromethanesulfonic acid, trifluoroacetic acid, and p-toluenesulfonic acid, and the anionic compound provides anions in the functionalized olefinic ionic liquid.
[0096] In this embodiment, configuring the functionalized alkenyl ionic liquid comprises the following steps:
[0097] S410: taking a cationic compound and an anionic compound, adding them to a mixture of deionized water and stirring, and then sequentially purifying, distilling, and drying to obtain a functional ionic compound;
[0098] S420: Take a lithium salt, dissolve it and a functional ionic compound in deionized water, and stir and dry to obtain a functionalized olefinic ionic liquid.
[0099] The specific process of configuring the functionalized alkenyl ionic liquid is described in detail in the preparation process and Fig. 9 content.
[0100] In this embodiment, the crosslinking agent is a mixture of any one or more of polyethylene glycol (diol) diacrylate, ethoxylated trimethylolpropane triacrylate, and pentaerythritol tetraacrylate; when polyethylene glycol (diol) diacrylate is selected, its average molecular weight is 200 to 1000.
[0101] In this embodiment, the lithium salt is a mixture of any one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide salt, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.
[0102] In this embodiment, the plasticizer is a mixture of any one or more of ether compounds, nitrile compounds and ionic liquids; wherein the ether compound is a mixture of any one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether; wherein the nitrile compound is a mixture of any one or more of malononitrile, succinonitrile, glutaronitrile, and adiponitrile.
[0103] In this embodiment, the ionic liquid is a mixture of any one or more of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium ionic liquids, quaternary phosphonium ionic liquids, pyrrolidine ionic liquids, and piperidine ionic liquids.
[0104] In this embodiment, the photoinitiator is a mixture of any one or more of phenyl (2,4,6-trimethylbenzoyl) phosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, hydroxycyclohexane phenone, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, hydroxymethyl benzoin methyl ether, and benzoin dimethyl ether.
[0105] Based on the total mass of the electrolyte precursor solution, the mass content of each component in the electrolyte precursor solution is: 40% to 60% of functionalized olefinic ionic liquid, 10% to 20% of cross-linking agent, 10% to 15% of lithium salt, 20% to 30% of plasticizer, and 0.5% to 2% of photoinitiator.
[0106] Step S50:
[0107] The initial solid electrolyte is thermally polymerized to obtain a thermally polymerized solid electrolyte, and then photopolymerized to obtain a PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte.
[0108] In this embodiment, the thermal polymerization is as follows: the impregnated functional PET nonwoven is placed between two parallel substrates and placed at 40° C. to 80° C. for 2 h to 6 h.
[0109] Thermal polymerization can make the active groups of the modified coupling agent of the functional PET non-woven fabric fully react with the active groups of the functionalized olefinic ionic liquid, so that the functionalized olefinic ionic liquid and the functional PET non-woven fabric are more fully cross-linked to form a preliminary single-cross-linked ionic liquid-non-woven fabric system.
[0110] In this embodiment, the photopolymerization is: placing the thermally polymerized solid electrolyte under ultraviolet light for 10 minutes to 60 minutes.
[0111] Photopolymerization can further polymerize the carbonyl groups of the functionalized olefinic ionic liquid cross-linked on the functional PET non-woven fabric in the single-crosslinked ionic liquid-non-woven fabric system and the cross-linking agent in the electrolyte precursor solution under the action of ultraviolet light to obtain a PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte with a high degree of polymerization.
[0112] In this embodiment, the nano zinc oxide particles are first impregnated and cross-linked onto the PET non-woven fabric to form a functional PET non-woven fabric, which forms the basis for subsequent cross-linking with the electrolyte precursor solution, and then the electrolyte precursor solution is cross-linked with the functional PET non-woven fabric by a distributed cross-linking method to form a PET-reinforced double-cross-linked polyionic liquid composite solid electrolyte. It can be seen that the active characteristics of the nano zinc oxide particles promote the cross-linking of the PET non-woven fabric with the functionalized olefinic ionic liquid, and the cations in the functionalized olefinic ionic liquid have good cross-linkable active groups. Through the effect of double cross-linking, a solid electrolyte with a high degree of cross-linking is formed. If the nano zinc oxide particles are modified with a silane coupling agent, the zinc oxide particles are more capable of forming a double cross-linking process with the subsequent functionalized olefinic ionic liquid because they contain active groups such as double bonds, epoxy, thiol and amino groups; that is, this embodiment forms a technical process for preparing a solid electrolyte by combining PET non-woven fabric with nano zinc oxide particles, cations and double cross-linking.
[0113] First, in order to further illustrate the performance difference of the functional PET non-woven fabric prepared in this embodiment, the following example in Table 1 is provided as an illustrative basis.
[0114] Table 1 is a comparison table of specific embodiments of functional PET nonwoven fabrics.
[0115]
[0116] From the comparison results in the above comparison table, it can be seen that: the functional PET non-woven fabric formed in Example ① has a good porosity, but is too thick and has a low tensile strength; the functional PET non-woven fabric formed in Example ② has a thinner thickness, a higher tensile strength, but a poor porosity; the functional PET non-woven fabric formed in Example ③ has a thinner thickness, a higher tensile strength, but a poor porosity; the functional PET non-woven fabric formed in Example ④ has a thinner thickness and a better porosity.
[0117] Therefore, it is shown that the addition of nano zinc oxide particles can ensure the tensile strength of the functional PET non-woven fabric at a thinner thickness and ensure good porosity.
[0118] Secondly, in order to further illustrate the preparation process of the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte prepared in this embodiment and the performance effect of the finished product, the following examples and comparative examples are provided as an illustrative basis.
[0119] Embodiment ⑤:
[0120] See also Figure 6 ; Figure 6 Schematic diagram of the synthesis process of forming VEIM-TFSI ionic liquid according to an embodiment of the present invention.
[0121] Preparation of functionalized olefinic ionic liquid: 1-vinylimidazole is taken, and 1-vinylimidazole is added to a mixture of epichlorohydrin and deionized water, wherein the mass of imidazole: epichlorohydrin: deionized water is 2:3:6, and the mixture is stirred at 60°C for 4 hours; then the mixture is purified with ethyl acetate, and then the residual deionized water and ethyl acetate are evaporated by reduced pressure distillation at 60°C, and then vacuum dried at 40°C for 12 hours to obtain 1-vinyl-3-epoxypropyl imidazole chloride (VEIM-Cl); VEIM-Cl and lithium bistrifluoromethylsulfonimide (LiTFSI) are dissolved in deionized water respectively to obtain a 20wt% aqueous solution, and then the LiTFSI solution is dropped into the VEIM-Cl solution, stirred at room temperature for 24 hours, and an ion exchange reaction is carried out; then the mixture is washed with deionized water, and vacuum dried at 60°C for 10 hours to obtain VEIM-TFSI ionic liquid, i.e., functionalized olefinic ionic liquid.
[0122] Preparation of electrolyte precursor solution: 4 g VEIM-TFSI ionic liquid, 1 g cross-linking agent polyethylene glycol (diol) diacrylate (molecular weight 600), 1 g lithium salt LiTFSI, 2 g plasticizer 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 0.1 g initiator benzoin methyl ether were mixed and dispersed evenly to obtain an electrolyte precursor solution.
[0123] Preparation of initial solid electrolyte: The functional PET nonwoven fabric prepared in Example ④ in Table 1 was immersed in the electrolyte precursor solution at 1×10 4 Let it stand for 10 minutes under a vacuum degree of Pa to allow it to be fully wetted.
[0124] Thermal polymerization: Take out the impregnated functional PET non-woven fabric and place it between two substrates, and add 50μm spacer pads on both sides to control the electrolyte thickness. Place it at 60℃ for 4h to allow the amino group of the modified coupling agent on the PET surface to fully react with the epoxy group of the functionalized olefinic ionic liquid, so that the functionalized olefinic ionic liquid and the functional PET non-woven fabric are cross-linked to form a preliminary single-cross-linked ionic liquid-non-woven fabric system.
[0125] Photopolymerization: The above-mentioned single cross-linked ionic liquid-non-woven fabric system is placed under ultraviolet light for 10 minutes for curing treatment, so that the carbon olefin group of the olefinic ionic liquid that has been cross-linked on the functional PET non-woven fabric and the cross-linking agent in the electrolyte precursor solution are further polymerized under the action of ultraviolet light to obtain a PET-reinforced double cross-linked polyionic liquid composite solid electrolyte (hereinafter referred to as: Example ⑤ electrolyte).
[0126] Embodiment ⑥:
[0127] As a comparative example of Example ⑤, all the steps of the above Example ⑤ were repeated, with the difference that the functional PET non-woven fabric with nano zinc oxide particles attached by light hot pressing was replaced with a PET non-woven fabric with light hot pressing but without nano zinc oxide particles attached, to prepare a PET composite solid electrolyte (hereinafter referred to as: Example ⑥ electrolyte).
[0128] Since the PET non-woven fabric of the electrolyte in Example ⑥ lacks the modified nanoparticles of the modified coupling agent active group, the VEIM-TFSI ionic liquid cannot be fully cross-linked on the PET non-woven fabric to form a single cross-linked ionic liquid-non-woven fabric system, and it is also impossible to further cross-link with the electrolyte precursor solution; however, since the unmodified PET non-woven fabric is immersed in the polymer electrolyte precursor solution, the precursor solution can still be infiltrated in the PET non-woven fabric and UV-cured to prepare a non-cross-linked polymer electrolyte membrane. At this time, the PET non-woven fabric and the polymer electrolyte are physically mixed, and there is no chemical bond grafting effect.
[0129] See also Figure 7 , Figure 7 The electrochemical impedance spectra of Example ⑤ electrolyte and Example ⑥ electrolyte according to the implementation mode of the present invention are shown.
[0130] Electrochemical tests and mechanical property tests were performed on the membranes of the electrolyte of Example ⑤ and the electrolyte of Example ⑥, respectively.
[0131] First, an electrochemical impedance spectroscopy test was performed. The results showed that the membrane impedance of the electrolyte in Example ⑤ was 2.03Ω, and its room temperature ionic conductivity was calculated to be 1.28×10 -3 S / cm; while the membrane impedance of the electrolyte in Example ⑥ is 3.18Ω, and its room temperature ionic conductivity is calculated to be 8.23×10 -4 S / cm,
[0132] See also Figure 8 ; Figure 8 Electrochemical window diagram of the preparation of Example ⑤ electrolyte and Example ⑥ electrolyte according to the implementation mode of the present invention.
[0133] Linear sweep voltammetry tests were performed on the films of Example ⑤ electrolyte and Example ⑥ electrolyte, respectively. The results showed that the electrochemical stability window of the film of Example ⑤ electrolyte could reach 5.3V, while the electrochemical stability window of the film of Example ⑥ electrolyte was only 4.6V.
[0134] See also Fig. 9 ; Fig. 9 Graphs showing stress-strain curves of Example ⑤ electrolyte and Example ⑥ electrolyte according to implementation modes of the present invention.
[0135] The membranes of Example ⑤ electrolyte and Example ⑥ electrolyte were subjected to tensile tests respectively. The results showed that the membrane tensile strength of Example ⑤ electrolyte was 27.6 MPa, while the membrane tensile strength of Example ⑥ electrolyte was only 16.3 MPa, which was quite different.
[0136] From the above three test results, it can be seen that the electrochemical properties and mechanical properties of the double-cross-linked solid electrolyte membrane of Example ⑤ electrolyte are significantly improved, which can effectively improve the migration efficiency of lithium ions in the electrolyte, enhance the oxidation stability of the electrolyte, and significantly reduce the risk of lithium dendrite piercing, thereby comprehensively improving the cycle stability of lithium-ion batteries.
[0137] Further, the electrolyte of Example ⑤ and the electrolyte of Example ⑥ were respectively loaded into Li||Li, Li||LiFeO 4 The (LFP) batteries were cycled and their performance differences were observed.
[0138] Among them, the components in the positive electrode LFP were ball-milled at 550 rpm for 6 hours in N-methylpyrrolidone according to the mass ratio of LFP: acetylene black: polyvinylidene fluoride = 8:1:1 to obtain a positive electrode slurry, which was coated on aluminum foil and vacuum dried at 80°C for 12 hours.
[0139] Preparation of symmetric Li||Li battery: Using the electrolyte of Example ⑤ or the electrolyte of Example ⑥, a button cell was assembled in a glove box with an argon atmosphere in the order of negative electrode shell / lithium sheet / electrolyte membrane / lithium sheet / stainless steel sheet / spring sheet / positive electrode shell, wherein the H 2 O and O 2 The content is less than 0.01ppm.
[0140] Preparation of all-solid-state lithium battery: The positive electrode on the aluminum foil was cut into a positive electrode sheet with a diameter of 8 mm, a lithium sheet was used as the negative electrode, and the electrolyte membrane in Example 1 or Comparative Example 1 was used to assemble the button battery in a glove box with an argon atmosphere in the order of negative electrode shell / lithium sheet / electrolyte membrane / positive electrode sheet / stainless steel sheet / spring sheet / positive electrode shell, wherein the glove box was filled with H 2 O and O 2 The content is less than 0.01ppm.
[0141] The test method is: using LAND battery charge and discharge instrument to test the lithium plating / stripping performance, charge and discharge performance and cycle performance of all-solid-state lithium batteries; symmetrical Li||Li battery at a current density of 0.5mAcm -2 , capacity density is 0.5mAhcm -2 Long cycle test was carried out under the condition of high current density; full-cell Li||LFP battery was charged and discharged in the range of 2.5V to 4.0V and 1.0C current density.
[0142] See also Fig.10 ; Fig.10 The symmetric Li||Li battery prepared by using the electrolyte of Example ⑤ and the electrolyte of Example ⑥ in the embodiment of the present invention is subjected to 0.5 mA -2 , 0.5mAhcm -2 The following cycle diagram.
[0143] It can be seen that the electrolyte of Example ⑤ circulates stably within 300 hours of circulation without obvious increase in overpotential; while the overpotential of the electrolyte of Example ⑥ suddenly drops from 39 mV to 10 mV at the 113th hour, resulting in an obvious short circuit, which is caused by the relatively low mechanical strength of the membrane in the electrolyte of Example ⑥.
[0144] See also Fig.11 ; Fig.11 Schematic diagram of the discharge curves and coulombic efficiency at 1C of the LFP full battery prepared with the electrolyte of Example ⑤ and the electrolyte of Example ⑥ according to the embodiments of the present invention.
[0145] It can be seen that for the LFP full battery, the full battery assembled with the electrolyte of Example ⑤ can be stably cycled 1000 times, with an average discharge capacity of 145.3 mAhg -1, and there is no obvious capacity decay. The average coulombic efficiency after 1000 charge and discharge cycles at 1C is 99.97%, indicating that the electrolyte of Example ⑤ has good cycle performance. In contrast, the full battery assembled with the electrolyte of Example ⑥ also has good cycle performance in the early stage, but the coulombic efficiency has a slight fluctuation. After 500 cycles, the discharge specific capacity has obvious decay, and the discharge specific capacity is only 122.1 mAh g at 700 cycles. -1 , the capacity retention rate is 85.74%, and the coulomb efficiency also shows obvious fluctuations, with an average coulomb efficiency of 97.82%.
[0146] The above results show that the electrolyte of Example ⑤ uses modified functional PET non-woven fabric, which can significantly improve the electrochemical and mechanical properties of the battery by double cross-linking with functionalized olefinic ionic liquid and polymer electrolyte, and greatly improve the cycle performance and safety performance of the battery.
[0147] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte, characterized in that: The preparation method comprises the following steps: S10: taking PET fibers, including first PET fibers and second PET fibers, wherein the first PET fibers have a greater aspect ratio than the second PET fibers, mixing the first PET fibers with the second PET fibers, and adding a dispersant, a defoaming agent, and water to dissolve the fibers to form a functional fiber slurry; S20: preparing the functional fiber slurry into PET base paper, and drying and hot pressing in sequence to form PET non-woven base paper; S30: configuring and forming a nano zinc oxide particle dispersion, and performing a dispersion treatment, and then immersing the PET non-woven fabric base paper in the nano zinc oxide particle dispersion, and performing a heat treatment to form a functional PET non-woven fabric; S40: configuring a functionalized olefinic ionic liquid, adding a crosslinking agent, a lithium salt, a plasticizer and a photoinitiator thereto, mixing and dispersing them uniformly, and obtaining an electrolyte precursor solution; placing the functional PET nonwoven in the electrolyte precursor solution, and allowing it to stand and immerse under vacuum conditions to obtain an initial solid electrolyte; S50: thermally polymerizing the initial solid electrolyte to obtain a thermally polymerized solid electrolyte, and then photopolymerizing the initial solid electrolyte to obtain the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte.
2. The method for preparing the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The diameter of the first PET fiber is 2 μm to 5 μm, and the diameter of the second PET fiber is 3 μm to 10 μm.
3. The method for preparing the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte according to claim 1 or 2, characterized in that: The mass ratio of the first PET fiber to the second PET fiber is 3:7 to 7:
3.
4. The method for preparing the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The mass ratio of the PET fiber in the functional fiber slurry is 1% to 3%; the mass ratio of the dispersant relative to the PET fiber is 0.1% to 1%; and the mass ratio of the defoaming agent relative to the dispersant is 45% to 55%.
5. The method for preparing the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The nano zinc oxide particles are zinc oxide particles modified by a silane coupling agent.
6. The method for preparing the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The functionalized alkenyl ionic liquid contains cations, and the cations are a mixture of any one or more of imidazole ions, pyridinium ions, quaternary ammonium ions, quaternary phosphonium ions, pyrrolidine ions, and piperidine ions.
7. The method for preparing the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte according to claim 6, characterized in that: The cation contains one or more groups of -NH2, -SH, -NCO, -OH, -C=C- or -CH(O)CH-.
8. The method for preparing the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte according to claim 1, characterized in that: Based on the total mass of the electrolyte precursor solution, the mass content of each component in the electrolyte precursor solution is configured as follows: 40% to 60% of functionalized olefinic ionic liquid, 10% to 20% of cross-linking agent, 10% to 15% of lithium salt, 20% to 30% of plasticizer, and 0.5% to 2% of photoinitiator.
9. The method for preparing the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte meets at least one of the following conditions: (A) Ionic conductivity is 1.0mS / cm to 1.5mS / cm; (B) The electrochemical window is 5V to 6V; (C) tensile strength of 15 MPa to 35 MPa; (D) Specific capacity of 150 mAh / g to 170 mAh / g; (E) Impedance is 3.5Ω to 4.6Ω.
10. Application of PET reinforced double cross-linked polyionic liquid composite solid electrolyte, characterized in that: The application is the use of the PET-reinforced double-crosslinked polyionic liquid composite solid electrolyte prepared according to any one of claims 1 to 9 in a gel polymer lithium-ion battery or a solid polymer lithium-ion battery.
Citation Information
Patent Citations
Polymer electrolyte preparing method and polymer electrolyte
CN105811005A
Polymer electrolyte membrane, preparation method thereof and lithium ion battery
CN110120548A
Preparation method of solid electrolyte, solid electrolyte and all-solid-state battery
CN113363573A
Battery diaphragm, preparation method thereof and battery
CN117175140A
Composite material, diaphragm as well as preparation method and application of diaphragm
CN118146600A
Cited By
Conductive polyester fiber and preparation method thereof
CN120311476A
MOF (Metal Organic Framework)-loaded PET (Polyethylene Terephthalate)-based diaphragm composite ether-cyano high-voltage electrolyte type gel electrolyte as well as preparation method and application thereof
CN122000453A